1976
DOI: 10.3758/bf03214428
|View full text |Cite
|
Sign up to set email alerts
|

Spatial interaction between cage and test environments: Position preferences of young isolated and pair-housed rats

Abstract: This study further investigates the relationship between cage size and activity in the open field. Male hooded rats were housed at weaning either individually or in pairs in small, medium, or large cages and observed after 15 days in an apparatus providing a choice between three environments of identical construction and dimensions to the different home cages. Three experimental conditions were employed. Both isolated and pair-housed rats were tested alone in the unfamiliar apparatus and some isolated rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Similarly, female rats showed a preference for an area with bedding material over an area with a grid floor both during the day and at night, while male rats only showed a preference for bedding material during the day and preferred the grid floor at night 72 . When given an option between a small, medium, and large arena in a choice test, the time spent in each arena depended on the size of the rat's home-cage and whether or not they were housed in isolation; paired-housed rats in large cages showed a preference for larger areas, whereas isolated rats housed in large cages showed a preference for the smaller area 73 . One study found that in the light phase, stainless steel cages -which offered increased darkness -were preferred, but in the dark phase, animals raised in stainless steel cages showed a preference for steel, while animals raised in polycarbonate cages showed no preference 74 .…”
Section: Refinements That Have Been Studied?mentioning
confidence: 99%
“…Similarly, female rats showed a preference for an area with bedding material over an area with a grid floor both during the day and at night, while male rats only showed a preference for bedding material during the day and preferred the grid floor at night 72 . When given an option between a small, medium, and large arena in a choice test, the time spent in each arena depended on the size of the rat's home-cage and whether or not they were housed in isolation; paired-housed rats in large cages showed a preference for larger areas, whereas isolated rats housed in large cages showed a preference for the smaller area 73 . One study found that in the light phase, stainless steel cages -which offered increased darkness -were preferred, but in the dark phase, animals raised in stainless steel cages showed a preference for steel, while animals raised in polycarbonate cages showed no preference 74 .…”
Section: Refinements That Have Been Studied?mentioning
confidence: 99%